Diversity and Resilience of Cuban Export and Import Economy: Portfolio Analysis of Export and Import Based on Herfindahl-Hirschman Index and Lauraeus-Kaivo-oja Index / Diversidad y resiliencia de la economía Cubana: análisis de la cartera de exportación e importación en base a los indices Herfindahl-Hirschman y Lausaeus-Kaivo-oja - Kaivo-oja Jari; Vehmas Jarmo; Saunders Anaely; Luukkanen Jyrki (Cuba, 2025)
This empirical study analyses both export and import portfolios of the Cuban economy. This article provides data-driven analyses of Cuban foreign trade activities. We combine Herfindahl-Hirschman Index (HHI) and Lauraéus-Kaivo-oja Index (LKI) measures to identify key changes and trends in export and import structures of the Cuban country-level trade relations. In this article, we report key results and findings of index-based analyses. This empirical study provides results of export and import structures of the Cuban economy and trade. Results are based on HHI and LKI analyses. These results give knowledge-based background for the export and import strategies of Cuba. Especially this kind of analysis gives a good knowledge base for smart specialization strategies of the Cuban economy. Results indicate that export-led strategies need some re-assessment from the resilience perspective of the Cuban export strategy. A more diversified export portfolio would be a smarter solution than the current concentration rate of the export portfolio. There is less need for re-assessment in the field of import strategy because the import portfolio of Cuba is already very diversified.
Programa General y Técnico: CONVENCIÓN CIENTÍFICA DE INGENIERÍA Y ARQUITECTURA DE LA CUJAE, 20 CCIA 2022